IMPROVING STUDENTS’ ABILITY TO WRITE VERB-FORM IN RECOUNT TEXT USING FLASHCARD - Nuriska, Reza; Bunau, Eusabinus; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is aimed to find out that the use of flashcard improves students? ability to write verb-form in recount text of VIII grade B students of SMP Negeri 05 Pontianak in Academic Year 2018/2019. This research was conducted based on the problems found in the classroom. The problems are the students wrote incorrect and did not know the meaning of verb-form in simple past tense. The method of this research is Classroom Action Research which consisted of four stages such as Planning, Acting, Observing, and Reflecting. This research was conducted in two cycles to 29 students. In collecting the data, the researcher used observation and measurement technique. The tools of collecting data were observation checklist, field notes and test. Based on the findings in this research, it was  found that using flashcard in teaching and learning in the classroom helped the teacher in manages class easily and they are could made students? interest to the lesson. It is also can change students? behavior in the classroom. Many of them seem motive and enthusiast when doing the test and discussion. They are not busy with their own business. Flashcard also improved students? ability to write verb-form in recount text.  Keywords: Recount Text, Verb-Form, Flashcard.